Allelochemicals: Biological Control of Plant Pathogens and Diseases - Inderjit; Mukerji, K.G (Disease Management of Fruits and Vegetables, 2006)
Biological control of plant diseases and plant pathogens is of great significance in forestry and agriculture. There is great incentive to discover biologically active natural products from higher plants that are better than synthetic agrochemicals and are much safer, from a health and environmental point-of-view. The development of natural products such as herbicides, fungicides, and their role in biological control of plant diseases, indicates a reduction in environmental and health hazards. Allelopathic techniques offer a real future in solving several problems, for instance biological control of plant pests. This book is organized around the indication that allelochemicals can be employed for biological control of plant pathogens and plant diseases. Specifically, this volume focuses on (i) discovery and development of natural product based fungicides for agriculture, (ii) direct use of allelochemicals as well as indirect effects through cover crops and organic amendments for plant parasitic pest control and (iii) application of allelopathy in pest management. .